أثر السياسة النقدية على التضخم في الجزائر دراسة قياسية - خلال الفترة 1990 - 2021 : The impact of monetary policy on inflation in Algeria a record study during the period 1990 to 2021 - نصيرة شرف,; عبد القادر روشو, (Journal of North African Economies, 2025)
This study aims to assess the impact of monetary policy on inflation in Algeria during the period (1990-2021). The self-regression model for the distributed slowing down (ARDL) was used to estimate the long-term relationship after ensuring a common complementarity between the study's variables. The results of the study indicated that monetary policy in Algeria is relatively ineffective in influencing inflation, mainly because of the reliance on monetary issuance to cover the public budget deficit free of charge for the monetary block. Inflation in Algeria is structural inflation resulting from non-monetary factors such as the dependence of the Algerian economy on the outside and the spread of the parallel market.